The Family Gap in Pay: Evidence from Seven Industrialized Countries - Susan Harkness; Jane Waldfogel (Luxembourg Income Study (LIS), 1999)
In this paper we use microdata on employment and earnings from a variety of industrialized countries to investigate the family gap in pay - the differential in hourly wages between women with children and women without children. We present results from seven countries: Australia, Canada, the United Kingdom, the United States, Germany, Finland, and Sweden. We find that there is a good deal of variation across our sample countries in the effects of children on women's employment. We also find large differences in the effects of children on women's hourly wages even after controlling for differences between women with children and women without children in characteristics such as age and education. Among the seven countries we study here, the United Kingdom displays the largest wage penalties to children. The family gap in pay is larger in the U.K. than in other countries because of the higher propensity of U.K. mothers to work in low-paid part-time jobs but also because even among full-timers, women with children in the U.K. are lower paid relative to other women than are mothers in other countries. Why does the family gap in pay vary so much across countries? We find that the variation in the family gap in pay across countries is not primarily due to differential selection into employment or to differences in wage structure. We therefore suggest that future research should examine the impact of family policies such as maternity leave and child care on the family gap in pay.
Keywords: 330; Fraueneinkommen; Weibliche Arbeitskräfte; Kinder; Familie; Australien; Kanada; Großbritannien; USA; Deutschland; Finnland; Schweden